1996
DOI: 10.1007/bf02248153
|View full text |Cite
|
Sign up to set email alerts
|

Airborne pollen in Kiev (Ukraine): gravimetric sampling

Abstract: This article presents the results of aeropalynological observations in Kiev, carried out with a gravimetric method, during January-October, 1994. The six most abundant pollen types were: Betulaceae (21%), Chenopodiaceae/Amaranthaceae (10%), Ambrosia (10%), Artemisia (9%,) Pinaceae (8%) and Poaceae (6%). Seasonal fluctuations of the atmospheric presence of tree/shrub and herb/grass pollen during the period March-September, 1993 and1994, are also shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The morphological characteristics of pollen grains are often used in taxonomy as additional diagnostic features (Nowicke 1975; Mosyakin and Tsymbalyuk 2015, 2017, Albach et al 2021; Tsymbalyuk et al 2021a, 2021b, 2022a, 2023; El Ghazali 2022; Kurşat et al 2022; Bahadur et al 2023), as well as for spore–pollen analysis in paleopalynology (Monoszon 1973; Bezusko et al 2003, 2006, 2019; Gerasimenko et al 2022; Usma et al 2022; Ahmad et al 2023). Many authors have reported representatives of the Chenopodiaceae/Amaranthaceae group as allergenic pollen producers (Savitsky et al 1996; Ianovici 2008; Rodríguez de la Cruz et al 2012; Angelini et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The morphological characteristics of pollen grains are often used in taxonomy as additional diagnostic features (Nowicke 1975; Mosyakin and Tsymbalyuk 2015, 2017, Albach et al 2021; Tsymbalyuk et al 2021a, 2021b, 2022a, 2023; El Ghazali 2022; Kurşat et al 2022; Bahadur et al 2023), as well as for spore–pollen analysis in paleopalynology (Monoszon 1973; Bezusko et al 2003, 2006, 2019; Gerasimenko et al 2022; Usma et al 2022; Ahmad et al 2023). Many authors have reported representatives of the Chenopodiaceae/Amaranthaceae group as allergenic pollen producers (Savitsky et al 1996; Ianovici 2008; Rodríguez de la Cruz et al 2012; Angelini et al 2014).…”
Section: Introductionmentioning
confidence: 99%